Interleukin 35 Synovial Fluid Levels Are Associated with Disease Activity of Rheumatoid Arthritis - Šenolt, Ladislav; Šumová, Barbora; Jandová, Romana; Hulejová, Hana; Mann, Heřman; Pavelka, Karel; Vencovský, Jiří; Filková, Mária (PloS one, 2015)
OBJECTIVES: To study the association of systemic and local interleukin-35 (IL-35) levels in rheumatoid arthritis. METHODS: 37 patients with treatment naïve early RA, 49 with established RA and 29 control patients with osteoarthritis (OA) were studied. Serum and paired synovial fluid samples were analysed for IL-35. Disease activity of RA patients was assessed according to the 28-Joint Count Disease Activity Score (DAS28). RESULTS: The levels of serum IL-35 were significantly higher in patients with treatment naïve early RA compared to those with established disease and control OA subjects. In addition, serum levels of IL-35 significantly decreased 12 weeks after initiation of glucocorticoids and conventional synthetic disease modifying antirheumatic drugs in patients with treatment naïve early RA. Synovial fluid IL-35 levels were significantly higher in RA compared to OA patients, were significantly elevated compared to serum counterparts and correlated with synovial fluid leukocyte count (r=0.412; p<0.01), serum CRP levels (r=0.362; p<0.05) and DAS28 (r=0.430, p<0.01). CONCLUSION: This is the first study showing elevated circulating levels of IL-35 in treatment naïve early RA, its significant decrease after treatment initiation and positive association between increased synovial fluid IL-35 and disease activity in patients with long-lasting RA.
Keywords: dospělí; Arthritis, Rheumatoid; Female; revmatoidní artritida; biologické markery; Biomarkers; Adult; ženské pohlaví; lidé; interleukiny; Immunosuppressive Agents; glukokortikoidy; synoviální tekutina; Glucocorticoids; stupeň závažnosti nemoci; Middle Aged; Male; Antirheumatic Agents; Synovial Fluid; lidé středního věku; Interleukins; mužské pohlaví; Severity of Illness Index; antirevmatika; imunosupresiva; Humans